2018
DOI: 10.3390/e20100768
|View full text |Cite
|
Sign up to set email alerts
|

Nestedness Maximization in Complex Networks through the Fitness-Complexity Algorithm

Abstract: Nestedness refers to the structural property of complex networks that the neighborhood of a given node is a subset of the neighborhoods of better-connected nodes. Following the seminal work by Patterson and Atmar (1986), ecologists have been long interested in revealing the configuration of maximal nestedness of spatial and interaction matrices of ecological communities. In ecology, the BINMATNEST genetic algorithm can be considered as the state-of-the-art approach for this task. On the other hand, the fitness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…1 should be mainly attributed to the fact that eigenvectors of different order are considered in the two approaches. Hence, the two metrics bring different information; albeit different, this information is relevant for both metrics, as demonstrated by numerous practical applications of the two approaches [20][21][22]24,[30][31][32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…1 should be mainly attributed to the fact that eigenvectors of different order are considered in the two approaches. Hence, the two metrics bring different information; albeit different, this information is relevant for both metrics, as demonstrated by numerous practical applications of the two approaches [20][21][22]24,[30][31][32][33] .…”
Section: Resultsmentioning
confidence: 99%
“…They found that "country-product" bipartite networks are significantly nested [87], and the dynamics of nestedness can predict the evolution of industrial ecosystems (see Refs. [88,89] for details on nestedness in networks). Moreover, the nestedness tends to be constant over time, making the pattern of industrial appearances predictable.…”
Section: Product Space and Economic Complexitymentioning
confidence: 99%
“…This ordering leads to the characteristic triangular shape (Medan et al., 2007) shown in Figure 1. The arrangement of the matrix which reveals and maximizes its nestedness is usually referred to as a maximally packed configuration , and various methods to produce it can be found in the literature (Domínguez‐García & Munoz, 2015; Lin, Tessone, & Mariani, 2018; Rodríguez‐Gironés & Santamaría, 2006).…”
Section: Introductionmentioning
confidence: 99%